Salivary RNA Signatures in Oral Cancer Detection - Prashanth Panta; Venkat Raghavender Venna (Analytical Cellular Pathology)
Oral squamous cell carcinomas (OSCC) are common malignancies that affect almost a million people every year. The key issue in reducing mortality and morbidity associated with OSCC is to develop novel strategies to identify OSCC at an early stage. One such strategy is the identification of biomarkers. So far, more than 100 biomarkers are recognized in the detection of oral cancer and they range from proteins to nucleic acids (DNAs, RNAs). Detection of ribose nucleic acids in saliva is a recent trend in diagnosing oral cancer. Studies have shown statistically significant changes in the levels of salivary transcriptomes in patients with oral squamous cell carcinomas. These biomarkers have displayed high sensitivity and specificity. Also, new point-of-care platforms such as oral fluid nanosensor test are now available that will soon emerge as chair-side tools for early detection of oral cancer. The aim of this review is to highlight the importance of salivary transcriptomes in oral cancer detection.